MANAJEMEN KINERJA DALAM SUMBER DAYA MANUSIA ISLAMI - Ayu Puspita Sari, Dewi; Ni'mati Rahmatika, Arivatu; Widyaningsih, Bekti (Universitas KH. A. Wahab Hasbullah, 2025)
Performance management is a crucial element in managing human resources (HR) to achieve organizational goals effectively and efficiently. This research aims to examine the application of Islamic principles in HR management and identify effective strategies in improving employee performance, with a focus on creating a harmonious and productive work environment. The method used is descriptive qualitative through a literature study approach. The results showed that the application of Islamic values, such as tawhid, ihsan, amanah, justice (adl), and deliberation (shura), contributed positively to the improvement of employee welfare, loyalty, and job satisfaction. Employee welfare, loyalty, and job satisfaction. Performance management based on Islamic principles not only increases productivity, but also forms an ethical and sustainable work culture. Keywords: Human Resources, Islamic Principles, Performance Management